From the Danube to the Yalu - Clark, Mark W. (London Harper and Brothers Publishers, 1954)
"From the Danube to the Yalu is General Clark's personal story of his seven years of almost constant struggle with the Communists in the battlefield and at the conference table--a struggle which began when he first came face to face with Soviet duplicity as U.S. High Commissioner for Austria in 1945..."
Include Index, Appendix and Illustration
Keywords: A United Nation Effort -- Two Years of Cold War -- Building the ROK Army